Biological markers of fertility (inhibin‐B) in HIV‐infected men: influence of HIV infection and antiretroviral therapy. Issue 6 (21st December 2015) - Moreno‐Pérez, O; Boix, V; Merino, E; Picó, A; Reus, S; Alfayate, R; Giner, L; Mirete, R; Sánchez‐Payá, J; Portilla, J
Abstract : Objectives: Inhibin B (IB) levels and the IB: follicle‐stimulating hormone (FSH) ratio (IFR), biomarkers of global Sertoli cell function, show a strong relationship with male fertility. The aim of the study was to examine the prevalence of impaired fertility potential in HIV‐infected men and the influence of antiretroviral therapy (ART) on fertility biomarkers. Methods: A cross‐sectional study with sequential sampling was carried out. A total of 169 clinically stable patients in a cohort of HIV‐infected men undergoing regular ambulatory assessment in a tertiary hospital were included. The mean [± standard deviation (SD)] age of the patients was 42.6 ± 8.1 years, all were clinically stable, 61.5% had disease classified as Centers for Disease Control and Prevention (CDC) stage A, and were na?ve to ART or had not had any changes to ART for 6 months (91.1%). Morning baseline IB and FSH concentrations were measured using an enzyme‐linked immunosorbent assay (ELISA) and an electrochemiluminescent immunoassay (ECLIA), respectively. A multivariate logistic regression model was used to identify factors associated with impaired fertility, defined as IB < 119 pg/mL or IFR < 23.5. Results: The mean (± SD) IB level was 250 ± 103 pg/mL, the median [interquartile range (IQR)] FSH concentration was 5.1 (3.3–7.8) UI/L and the median (IQR) IFR was 46.1 (26.3–83.7). The prevalence of impaired fertility was 21.9% [95% confidence interval (CI) 16.3–20.7%]. Negative correlations of body mass index and waist: hip ratio with FSH and IB levels were observed ( P < 0.01), while a sedentary lifestyle and previous nevirapine exposure were associated with a decreased risk of IB levels ≤ 25th percentile in multivariate analysis. Only older age, as a risk factor, and sedentary lifestyle, with a protective effect, were independently associated with impaired fertility in multivariate analysis. Conclusions: Global testicular Sertoli cell function and fertility potential, assessed indirectly through serum IB levels and IB: FSH ratio, appear to be well maintained in HIV‐infected men and not damaged by ART.